Budaya Ngopi : Pola Konsumsi Konsumen Kafe, Kedai Kopi dan Warung Kopi di Kabupaten Tulungagung - Novi Reza Pramasari; Wildan Wardhani; Agus Eko Sujianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
It’s becoming more common to observe people congreagating at different cafes, coffe shoops, kopitiams, or food stalls in Indonesia. For the residents of Tulungagung, getting together, hanging out, drinking coffee, and similar activities are done frequently to establish new consuming habits. Finding out the consumption habits of consumers of cafes, coffee shops, and food stall in Tulungagung was the aim of this study. The development and flourishing of coffee culture in Tulungagung was explained by researchers via the lens of consumption habits, consumer culture, identity, and the concept of a